Listen to What Anatolia Is Saying for a Sustainable Future for All - Ayyildiz, Pınar; Yilmaz, Adem (IGI Global, 2024)
This chapter intends to illustrate and get inspired by rituals and beliefs belonging to several societies and cultures rooted in Anatolia to facilitate students' understanding of what climate and climate change mean for local and global communities. In fact, the protection and the transfer of socio-cultural identities of local people and groups via assuring an intergenerational means of knowledge dissemination through oral communication/dialogues, observations, and participation will be both a meaningful and a purposeful act. With the help of activities like readings, on-site visits, storytelling, and portfolio work that can be integrated into the current program, the researchers attempt to welcome learners studying at high school as the key agents of the process to help develop pro-environmental values and related behaviors, as well as discussing the collective consciousness of the past and present civilizations of Anatolia, whilst embracing a non-Western outlook.
Keywords: 4. Education